If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+3(-x+8)=0
We simplify the equation to the form, which is simple to understand
-x+3(-x+8)=0
Reorder the terms in parentheses
-x+(-3x+24)=0
Remove unnecessary parentheses
-x-3x+24=0
We move all terms containing x to the left and all other terms to the right.
-1x-3x=0-24
We simplify left and right side of the equation.
-4x=-24
We divide both sides of the equation by -4 to get x.
x=6
| 3+4+a=12 | | (C+5)+(c-1)=90 | | 4y+6(y+8)= | | 3(x+1)+4x=24 | | 18.1--0.7=c | | 75c^2+90cd+27d^2= | | 18.1--0.7= | | 16x^2-38x-5= | | 9=-7y+8 | | y=(3)(-1)-2 | | 79=8x-11 | | 5m-8.5=3.7m+4.37 | | 16x^2-38c-5= | | 2m^2-29m+60=0 | | y=(3)(1)-2 | | 1.5x+.7=10.7+.5x | | 7x+6=8-(7x-6) | | -2(5k-1)=22 | | 5n+7+7=3n-2+2(2n+1) | | y=(3)(0)-2 | | 5y-81x=0 | | 50x+6=6+50x | | x-5+14=24 | | 2a^2-25a+50=0 | | 4+2.3t=1.7 | | (3x-5)+(8x-13)=180 | | 5u+18=58 | | (3d+4)+(2d-9)=180 | | 4b-6+2r=-48 | | 3x+12=5x+42 | | a+2s=3(s-2)+1 | | x^2+17x-193=0 |